Perfect opportunity - Havill, Steven (Havill, Steven. Posadas County series, 2024)
"The morning after his eighty-seventh birthday bash, former Posadas County sheriff Bill Gastner drives past a couple of vehicles stopped on the highway shoulder. It's not an unusual sight: a sheriff's patrol unit, emergency lights ablaze, pulled in behind a pickup truck. The female deputy hasn't radioed for backup. But there's something about the scene that makes him feel uneasy. The next day, Undersheriff Estelle Reyes-Guzman is called to a rather more dramatic and disturbing roadside scene, with the same truck the star of the show. But this time, its occupant is in no fit state to talk - his dead body stabbed through the chest with a Ka-Bar, a second corpse in the ditch beside the car. What happened to the two men? And what were the dead man and the deputy discussing in the quiet of pre-dawn the previous day? The truth is more twisty and complex than even Estelle and her long-standing friend and former colleague Bill are ready for, and it will take all their combined years of experience to untangle the sorry tale and ensure justice is served."--